Illegality and inequity in Ghana's cocoa-forest landscape: How formalization can undermine farmers control and benefits from trees on their farms. (July 2018) - Hirons, M.; McDermott, C.; Asare, R.; Morel, A.; Robinson, E.; Mason, J.; Boyd, E.; Malhi, Y.; Norris, K
Abstract: Schemes to promote sustainable forest management have increasingly focused on addressing widespread informalities in timber production, based on the presumed links between formalisation, the maintenance of forest cover and local welfare. This trend is typified by the EU Forest Law Enforcement, Governance and Trade (FLEGT) initiative and associated Voluntary Partnership Agreements (VPA) aimed at eradicating the trade of illegal wood between partner countries and the EU. Yet there is concern that such initiatives might have detrimental impacts on the largely informal rights of local resource users. In order to inform the formalisation agenda, more detailed analysis of the operation of local rights, and how they might be affected by particular schemes is required. This paper focuses on Ghana as a country with a largely informal wood sector that has signed a VPA with the EU for the express purpose of rapid formalisation. Our analysis is guided by a framework for assessing which types of rights might be transformed by particular approaches to formalisation and the subsequent effect this might have on forests and people in particular local contexts. We then apply this framework to an in-depth local case study of on-farm timber governance within a cocoa-forest landscape in Ghana's Central Region to examine how the operation of formal and informal and substantive and procedural rights shape who controls, and benefits from, on-farm timber production. We then analyse the content of the VPA in light of these local realities and assess its potential impacts. Our findings highlight how the substantive rights the state grants to companies are presumed to be balanced with the granting of procedural rights to farmers via the mechanisms of right of refusal to harvest on-farm timber, compensation for damage to cocoa crops and the negotiation of community-level Social Responsibility Agreements with private companies. Yet a comparison of these formal rights with farmers' existing informal rights reveals that farmers' control and access to benefits from trees on their farms are notably higher in the 'illegal' chainsaw dominated informal sector than in the 'legal' state-based system. Farmers choose to maintain trees on farms both to shade cocoa and in anticipation of benefits from their informal sale. The VPA, however, aims to eradicate all informal on-farm timber production and thus threatens existing local rights and benefit capture while diminishing incentives to maintain trees on farm. Rather than further criminalising local systems of timber governance, the maintenance of tree cover and local benefit-sharing would be better served by 1) phasing out timber concessions on farmland, 2) abandoning the distinction between planted and native trees on farms and, 3) understanding, recognizing and respecting the existing informal rights of farmers, traditional authorities and chainsaw loggers to negotiate among themselves patterns of access and control of on-farm trees and timber. In general, the case study challenges the assertion that formalisation is requisite for sustainable forest management and mandates a more nuanced and contextually informed assessment of the assumed costs and benefits associated with particular forms of legal and policy reform.